2022
DOI: 10.1093/femsyr/foac044
|View full text |Cite
|
Sign up to set email alerts
|

The evolution and role of the periplasmic asparaginase Asp3 in yeast

Abstract: The study of nitrogen assimilation in yeast is of interest from genetic, evolutionary, and biotechnological perspectives. Over the course of evolution, yeasts have developed sophisticated control mechanisms to regulate nitrogen metabolism, with domesticated lineages sometimes displaying particular specialisation. The focus of this study was on assimilation of asparagine, which is a significant nutritional source for some alcoholic fermentations. We were particularly interested in ASP3, which encodes a periplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The relatively better growth of S. uvarum on methionine suggests higher efficiency of the transaminases Aro8p and Aro9p or more fine-tuned regulation of the enzymes in this species. Regarding asparagine, the better growth of S. cerevisiae could possibly be attributed to the presence of ASP3 in some strains, but that cannot be the full explanation since, like S. uvarum, S. cerevisiae EC1118 lacks this gene (Coral-Medina et al, 2022 ; League et al, 2012 ). It is also noteworthy that outliers to these species-level findings can be observed at the strain level.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively better growth of S. uvarum on methionine suggests higher efficiency of the transaminases Aro8p and Aro9p or more fine-tuned regulation of the enzymes in this species. Regarding asparagine, the better growth of S. cerevisiae could possibly be attributed to the presence of ASP3 in some strains, but that cannot be the full explanation since, like S. uvarum, S. cerevisiae EC1118 lacks this gene (Coral-Medina et al, 2022 ; League et al, 2012 ). It is also noteworthy that outliers to these species-level findings can be observed at the strain level.…”
Section: Discussionmentioning
confidence: 99%
“…Our genetic characterization of Wyeast 3068 showed deletions of many genes as expected for ale yeast: flocculation genes vary between brewing strains 43 and can be lost in aged brewing yeast 44 , less efficient carbohydrate transporters are lost in some brewing strains 45 , ASP3 has been lost in many S. cerevisiae isolates 46 , and transposition events and copy number variations of Ty elements are common in industrial yeast strains 47 . Previous studies have demonstrated that genome evolution in brewing yeast strains does occur across the repitching process as selected populations have adapted to the fermentation environment 19 .…”
Section: Discussionmentioning
confidence: 70%
“…It encodes an L-asparaginase that catalyzes the hydrolysis of asparagine to aspartic acid releasing ammonia [ 47 ]. This could be of adaptive value in cider yeasts as asparagine is an abundant amino acid in apple must [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%